Efeitos dos inseticidas utilizados no controle de Bemisia tabaci (Gennadius) biótipo B e sua seletividade aos inimigos naturais na cultura da soja - Vieira, Simone Silva; Carissimi Boff, Mari Ines; Bueno, Adeney Freitas; Gobbi, Alysson Luis [UNESP]; Lobo, Rafael Vicentini; Oliveira de Freitas Bueno, Regiane Cristina (Universidade Estadual de Londrina (UEL), 2012)
In recent crop seasons, the whitefly, Bemisia tabaci biotype B has become a serious pest in soybean crops due to high infestations and its control difficulties. Therefore, it is important to search control alternatives in the integrated pest management approach. Thus, it was evaluated in this study the efficacy of the whitefly control using different insecticides in greenhouse conditions and their selectivity to the parasitoids Encarsia formosa, Trichogramma pretiosum and Telenomus remus. Buprofezin 150 g.a.i. ha(-1) + mineral oil 0.2% v/v and pyriproxyfen 100 g.a.i. ha(-1) were considered the best options for the whitefly management due to combine good pest control efficacy with higher selectivity to the parasitoids except Encarsia formosa for which no treatment was classified as harmless. Betacyflutrin 9.375 + imidacloprid 75 g.i.a. ha(-1) was efficient on controlling whiteflies nymphs but was not harmless to the studied natural enemies. In general, the treatments including pyretroids compounds (betacyflutrin 9.375 + imidacloprid 75 + spiromesifen 60, betacyflutrin 9.375 + imidacloprid 75 and lambda-cyhalothrin 26.5 + thiametoxan 35.25 g.a.i. ha(-1)) were the most harmful to the evaluated parasitoids and therefore it use should be avoid whenever possible.
Effects of insecticides used in Bemisia tabaci (Gennadius) biotype B control and their selectivity to natural enemies in soybean crop
Keywords: Insecticides; parasitoids; whitefly; integrated pest